Genetic identification and restriction fragment length polymorphism (RFLP) based analysis of Myxovirus resistant gene (Mx) of chicken in Bangladesh - Alam, J; Hasan, M; Hasan, K; Giasuddin, M; Rahman, MH; Alam, MS; Taimur, MJFA (Bangladesh Journal of Livestock Research, 2020)
The Myxovirus resistant gene (Mx) codes for Mx protein with antiviral activity. Mx gene has been found in yeast and vertebrates ranging from fish to humans. In the present study Mx gene and its diversity in chicken is reported. A total of 42 blood samples were collected from different groups of chicken and were analyzed by polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP). The diversity of Mx gene was enumerated by RFLP of PCR product with RsaI and SspI restriction enzyme. Mx gene was amplified from all the tested samples (100%) with the primers used. The primers amplified specific 100bp and 300bp DNA fragments from Mx gene. RFLP analysis of PCR product obtained with mismatched primers revealed that three types of Mx gene allele are prevailing in the tested samples; these are homozygous resistant Mx allelic gene (R/R), heterozygous Mx allelic gene (R/S) and homozygous sensitive Mx allelic gene (S/S). The proportions of each gene allele in the sampled chicken were 42.86% R/R, 42.86% S/S and 14.29% R/S. Interestingly, variation in Mx gene was observed within and between the groups of chicken. Present study has limitations like number of sample, species of bird sampled, etc. However, the study provides the genetic basis to some extent of chicken about resistance or sensitivity to avian influenza. To the best of our knowledge this is the first report of Mx gene related study in chicken in Bangladesh. Bangladesh J. of Livestock Res. 20(1-2): 18-25, Jan-Dec 2013